Exploring staff perspectives of the barriers and facilitators to implementation of total quality management in two Jordanian hospitals - Algunmeeyn, Abdullah Ahmad Abdullah (2019)
Background and Rationale: ‘Total quality management‘ (TQM) is defined as the philosophy of seeking to satisfy customers’ needs and continually improve quality (Stevenson, 2002). In the 1980s, the concept of TQM first emerged in Japan’s industrial sector, moving to the West and Australia in the 1990s. It grew in importance and many companies strove to implement it as a means of developing and upgrading their services. It is significant for healthcare organisations in the enhancement of their care service quality, as well as helping them to improve their management, achieve more effective organisation, increase staff satisfaction, promote commitment to the organisation, encourage teamwork among staff and management, and increase patient satisfaction.